Hommage à Bojan Golija - Balažic, Janez; Rimele, Oto (2017)
The exhibition of homage by Bojan Golija (1932-2014) is a noble representation of the professor's choir at the Department of Fine Arts of the Faculty of Education and presents his human, professorial and artistic dignity. The selected works are, of course, highly evident and representative for the opus of participating artists, graphic artists Samuel Grajfoner and Petra Varl, sculptors Dragica Čadež Lapajne, Viktor Gojkovič, Darko Golija and Dušan Zidar, art photographers of God Čerin and Tanja Verlak, designers of dolls Breda Varl and painters Laci Pandur , Anka Krašna Kocijan, Ota Rimeleta and Sandi Červek. Because the art, created in any kind of methea genre, is 'the body and the place of meditation, where imperceptibly it is a constant need for questioning about the meaning of existence, transience, duration, degree of testimony', and at the same time it is the marker of the artist's being. Selected artworks in the homage in Bojana Golija provide good views on artistic production, orientation and insight into the visual reception of the current professor's choir at the University of Maribor.
Keywords: Hommage; Bojan Golija; art; graphics; sculptors; painters